IMPACT OF EFFLUENT DISCHARGE AND SEASONAL VARIATIONS ON THE QUALITY OF EKEMAZU STREAM IN DELTA STATE, NIGERIA. - HILDA ABIOLA EMMANUEL-AKERELE (Diponegoro University, 2022)
The impact of effluent discharge and seasonal variations on the quality of Ekemazu was determined. Total heterotrophic bacterial counts and most probable number was determined using standard microbiological procedures. The total heterotrophic bacteria counts in the upstream samples analyzed across the seasons varied between 4.8 ± 0.4 x 102 cfu/ml and 8.7 ± 0.1 x 102 cfu/ml, 36.0 ± 1.0 x 102 cfu/ml and 98.0 ± 1.0 x 102 cfu/ml in the effluent discharge point, 53.0 ± 6.0 x 102 cfu/ml and 85.0 ± 3.0 x 102 cfu/ml in the domestic activities point and 46.0 ± 4.0 x 102 cfu/ml and 78.0 ± 2.0 x 102 cfu/ml in the downstream. The total coliform counts ranged between 11.3 ± 0.9 MPN/100 ml and 19.0 ± 1.0 MPN/100 ml in the upstream, 20.0 ± 0 MPN/100 ml and 37.5 ± 2.5 MPN/100 ml in the effluent discharge point, 18.0 ± 0 MPN/100 ml and 35.0 ± 0 MPN/100 ml in the domestic activities point and 17.0 ± 0 MPN/100 ml and 22.5 ± 2.5 MPN/100 ml in the downstream. The faecal coliform counts in the upstream ranged between 6.0 ± 0 MPN/100 ml and 8.0 ± 1.0 MPN/100 ml, 9.0 ± 1.0 MPN/100 ml and 13.0 ± 1.0 MPN/100 ml in the effluent discharge point, 9.0 ± 0 MPN/100 ml and 11.5 ± 0.5 MPN/100 ml in the domestic activities point, 8.0 ± 0 MPN/100 ml and 10.0 ± 0.8 MPN/100 ml in the downstream. Organisms identified were Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Proteus mirabilis, Aeromonas hydrophilia, Klebsiella pneumoniae and Enterococcus faecalis. Antimicrobial susceptibility test of isolates showed that the organisms were 14% sensitive to Meropenem, Levofloxacin, Amoxicillin, Tetracycline, Ciprofloxacin, Erythromycin and Gentamicin, 29% sensitive to Septrin and Chloramphenicol 43% sensitive to Amikacin, Ampicillin, and Gentamicin, This research clearly showed that bacterial load of the stream is higher than the WHO acceptable limit and the isolates are multidrug resistant.